Reading an Artist’s Intention from the Composition (RAIC): eye movements and aesthetic experience in Japanese woodblock prints - Nojo, Yuka; Chan, Antoni B. (Frontiers in Psychology, 2025)
BackgroundUnderstanding the cognitive mechanisms and decision-making processes involved in aesthetic judgement of visual art has become a growing focus in recent research. While eye movements have been strongly associated with impression evaluations, the underlying processes linking gaze behaviour and aesthetic experience remain underexplored. Recent discourse suggests that compositional strategies in artworks may guide viewers’ gaze and support narrative understanding.ObjectiveWe hypothesised that the more closely a viewer’s gaze follows the artist’s intended compositional path, the better they comprehend the artwork’s intention and context, thereby enriching their aesthetic experience. This process is defined as RAIC (Reading an Artist’s Intention from the Composition).MethodsWe collected 30-s eye-tracking data from 48 participants who viewed 12 Japanese woodblock landscape prints (Ukiyo-e). These artworks were selected from a preliminary study of 101 prints, based on the six highest and six lowest aesthetic ratings. Eye movements were segmented into 3-s intervals. Using the VBHEM algorithm, a variational Bayesian extension of the Eye Movement Hidden Markov Model (EMHMM), we evaluated the similarity between participants’ gaze sequences and expert-estimated scanpaths provided by specialists from the Japanese Painting Conservation and Restoration Laboratory of the Tokyo University of the Arts. Pupil size was analysed as an index of perceptual fluency.ResultsArtworks with compositional structures aligned with expert scanpaths enabled viewers to better interpret the artist’s intention, promoting deeper aesthetic engagement. Additionally, high-rated artworks elicited greater perceptual fluency.ConclusionThese findings support the RAIC hypothesis, suggesting that guided visual exploration facilitates interpretation of artistic intention and contributes to a more meaningful aesthetic experience.